PENINGKATAN HASIL BELAJAR IPA MELALUI PENDEKATAN KETERAMPILAN PROSES SEKOLAH DASAR NEGERI KUAMANG PASAMAN - Kasmil, Trio (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research aim was to describe the improve of learning achievement in science study by using skill proccess approach at public elementary school in Kuamang Pasaman. This study used the classroom action research methode in two cycles study. Each cycle consisted of planning action, observation, and reflection term. The data was analyzed by using qualitative and quantitative approach. The research subject's is 30 students. The result of this research showed that the skill proccess approach improves the learning achievement.   Kata kunci : hasil belajar, IPA; pendekatan keterampilan proses